The intersection of turn-taking and repair: the timing of other-initiations of repair in conversation - Kendrick, Kobin H. (Frontiers in Psychology, 2015)
The transitions between turns at talk in conversation tend to occur quickly, with only a slight gap of approximately 100 to 300 ms between them. This estimate of central tendency, however, hides a wealth of complex variation, as a number of factors, such as the type of turns involved, have been shown to influence the timing of turn transitions. This article considers one specific type of turn that does not conform to the statistical trend, namely turns that deal with troubles of speaking, hearing, and understanding, known as other-initiations of repair. The results of a quantitative analysis of 169 other-initiations of repair in face-to-face conversation reveal that the most frequent cases occur after gaps of approximately 700 ms. Furthermore, other-initiations of repair that locate a source of trouble in a prior turn specifically tend to occur after shorter gaps than those that do not, and those that correct errors in a prior turn, while rare, tend to occur without delay. An analysis of the transitions before other-initiations of repair, using methods of conversation analysis, suggests that speakers use the extra time (i) to search for a late recognition of the problematic turn, (ii) to provide an opportunity for the speaker of the problematic turn to resolve the trouble independently, (iii) and to produce visual signals, such as facial gestures. In light of these results, it is argued that other-initiations of repair take priority over other turns at talk in conversation and therefore are not subject to the same rules and constraints that motivate fast turn transitions in general.